The potential of fuel cell by using biogas from palm oil waste to generate electricity - Chai, Jun Xuan; Mohd Shafie, Shafini (Universiti Utara Malaysia, 2020)
This study assessed the potential of the fuel cell by using biogas from palm oil waste to generate electricity. The objectives of the study are to identify the types and waste management of palm oil waste, to explore the process of producing biogas from the palm oil wastes and to identify the potential of the biogas as fuel for fuel cells to generate electricity. A survey and interview were used to collect data in this study. A survey through a phone call was conducted with the palm oil mills in Malaysia. An interview was done with the respondent to ask about the biogas production. The findings of this study are the empty fruit brunch (EFB) is the largest amount from all palm oil waste but they are still using palm oil mill effluent (POME) to produce biogas. Besides, most of the palm oil mill owners still don't know biogas can be used to the power fuel cell to generate electricity.